2011
DOI: 10.1097/brs.0b013e3181da79af
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Kinematic Features Between the in vivo Active and Passive Flexion-Extension of the Subaxial Cervical Spine and Their Biomechanical Implications

Abstract: In gentle flexion, the active and passive cervical spinal motions are closely approximated, which implies that the active neuromuscular control mainly plays the buffer-and-brake mechanism without placing additional load on the spine. In contrast, the degree of passive extension is limited, and active neuromuscular control may place additional load on the spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Both trapezius and multifidus muscle are extensors, and the result implied that the effect on joint motion of muscular pain may be more profound, when the muscles work as agonist (Côté and Bement, 2010). Alternatively, anatomical difference between anterior and posterior osseous, muscular and ligament structures under the influence of gravity may account for different motion findings between cervical flexion and extension (Hsu et al, 2011). The results agree with previous studies, which showed that neck pain affected cervical motion differently between flexion and extension (Rudolfsson et al, 2012).…”
Section: Dynamic Joint Kinematicssupporting
confidence: 91%
“…Both trapezius and multifidus muscle are extensors, and the result implied that the effect on joint motion of muscular pain may be more profound, when the muscles work as agonist (Côté and Bement, 2010). Alternatively, anatomical difference between anterior and posterior osseous, muscular and ligament structures under the influence of gravity may account for different motion findings between cervical flexion and extension (Hsu et al, 2011). The results agree with previous studies, which showed that neck pain affected cervical motion differently between flexion and extension (Rudolfsson et al, 2012).…”
Section: Dynamic Joint Kinematicssupporting
confidence: 91%
“…Plain film radiography [7,8], cineradiography [9,10], videofluoroscopy [11], computerised tomography [12], magnetic resonance imaging [13], video and electromyography [14], digital inclinometry [15], stereophotogrammetry [16], electrogoniometry [17] and motion analysis systems [1-3, 18, 19] have been used to measure cervical spine motion. Each has their advantages and disadvantages, but the fact that so many techniques and systems exist suggests that the optimal method to measure cervical spine motion has yet to be found.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in resistance demand different motor control strategies to conduct cervical flexion and extension movements 60 . Second, the cervical joint motion depends on proper co-contraction between agonist and antagonist muscles 52 .…”
Section: Accepted Manuscript 12mentioning
confidence: 99%